Underlying Internationalization Process Theories for Small and Medium Enterprises (SMEs): A Systematic Literature Review and Classification of Research Streams - Evy Rachmawati Chaldun; Gatot Yudoko; Eko Agus Prasetio (Jurnal Manajemen Indonesia, 2022)
Studies on the internationalization process of SMEs have fascinated the attention of researchers around the world. The dynamics in the internationalization process of SMEs have attracted researchers' interest in analyzing the behavior and the factors that influence it with various theoretical approaches to contribute to the development of international business studies. This paper intended to provide an overview of the various theories applied in investigating SMEs' internationalization process. The review was conducted on 100 journal articles between 2013 and 2020. The investigation results show that 17 different theories have been identified in the internationalization process of SMEs and we classified them into five streams. Based on our findings, from those 17 theories, the five primary published theories in order are (1) Uppsala theory, (2) Network theory, (3) Resource-based theory, (4) international entrepreneurship theory, and (5) institutional theory. This study also provides suggestions and implications for future research. Keywords— Internationalization process; Internationalization SME theory; Small and Medium Enterprises (SMEs)